Synthesis of B-RGO-MWCNT/CuFeO2 Composite for Efficient Hydrogen Evolution Reaction. (2nd November 2021) - Sakthinathan, Subramanian; Rajakumaran, Ramachandran; Keyan, Arjunan Karthi; Vasu, Dhanapal; Chen, Shen-Ming; Chiu, Te-Wei
Abstract : The key to utilizing renewable energy is the development of promising new materials for electrocatalytic water splitting. Boron doped reduced graphene oxide/multiwalled carbon nanotubes (B-RGO-MWCNT) composite decorated with CuFeO2 complex modified glassy carbon electrode (GCE) was applied to the water electrolysis (HER). The B-RGO-MWCNT composite was prepared using the hydrothermal method and the CuFeO2 delafossite material was synthesized by a glycine nitrate process. Moreover, the material structures of B-RGO-MWCNT/CuFeO2 composite were identified by different spectroscopic and microscopic measurements. The B-RGO-MWCNT/CuFeO2 composite was structurally well-formed with an active surface area. The GCE electrode decorated with B-RGO-MWCNT/CuFeO2 composite was applied to HER and exhibited an outstanding electrocatalytic response with low over-potential and a small Tafel slope of 54 mV·dec −1 at 10 mA.cm −2 over potential with high stability. Moreover, the small Tafel slope suggests a promising electrocatalyst suitable for practical use. Furthermore, the obtained B-RGO-MWCNT/CuFeO2 electrode was correlated with Pt/C and exhibited superior electrocatalytic performance toward the HER in acidic media. The electrochemical response is credited to the active sites and effective electron transport between CuFeO2 and B-RGO-MWCNT. As a result, the B-RGO-MWCNT/CuFeO2 composite looks to be an effective catalyst for the electrocatalytic reaction of HER and has the potential to produce clean energy.